Pengaruh PDRB Perkapita dan Indeks Pebangunan Manusia (IPM) terhadap Pemerataan Pendapatan di Provinsi Jawa Timur - Afini, Nur (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2019)
The purpose of this study, To Know Per capita GRDP and Human Development Index (HDI) partially and simultaneously influences the income distribution in East Java Province. While the method is panel data regression with medel random effects. The results of the study simultaneously all independent variables including GRDP Per Capita, Human Development Index significantly influence jointly on Income Equity. While partially, the Per capita GRDP has a significant influence on income distribution in Java. The Human Development Index does not have a significant effect but is positively related to income distribution in the province of East Java.